2019
DOI: 10.26508/lsa.201900380
|View full text |Cite
|
Sign up to set email alerts
|

Cellular response upon proliferation in the presence of an active mitotic checkpoint

Abstract: Eukaryotic cells treated with microtubule-targeting agents activate the spindle assembly checkpoint to arrest in mitosis and prevent chromosome mis-segregation. A fraction of mitotically arrested cells overcomes the block and proliferates even under persistent checkpoint-activating conditions. Here, we asked what allows proliferation in such unfavourable conditions. We report that yeast cells are delayed in mitosis at each division, implying that their spindle assembly checkpoint remains responsive. The arrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Regardless of the prolonged mitotic arrest, many cells slip through and continue proliferating. Cell division, however, takes place when microtubules are not properly polymerized and thus chromosomes tend to missegregate [32], which we confirmed by following the inheritance of GFP-tagged chromosome V by live cell imaging during the first cycle after decreasing temperature ( Figure S1B). Hence, we interpreted the initial slow growth rate as a consequence of prolonged activation of the mitotic checkpoint.…”
Section: Yeast Cells Become Resistant To Stimuli Inducing Microtubulesupporting
confidence: 58%
See 3 more Smart Citations
“…Regardless of the prolonged mitotic arrest, many cells slip through and continue proliferating. Cell division, however, takes place when microtubules are not properly polymerized and thus chromosomes tend to missegregate [32], which we confirmed by following the inheritance of GFP-tagged chromosome V by live cell imaging during the first cycle after decreasing temperature ( Figure S1B). Hence, we interpreted the initial slow growth rate as a consequence of prolonged activation of the mitotic checkpoint.…”
Section: Yeast Cells Become Resistant To Stimuli Inducing Microtubulesupporting
confidence: 58%
“…Thus, average size can be used as a proxy for checkpoint activation. [32]. Accordingly, we observed that ancestors tub2-401 were larger than controls expressing TUB2.…”
Section: Yeast Cells Become Resistant To Stimuli Inducing Microtubulementioning
confidence: 60%
See 2 more Smart Citations
“…At low temperature, it is non‐functional and results in improper microtubule polymerization (Huffaker et al , 1988; Sullivan & Huffaker, 1992). This leads to the activation of both the mitotic checkpoint (Corno et al , 2019) and the spindle position checkpoint, since deletion of two of their essential genes ( MAD2 and BUB2 , respectively) impairs growth even at the semi‐permissive temperature of 23°C (Fig EV1B). By using live‐cell imaging at the restrictive temperature (18°C), we confirmed that cells were large and budded, a phenotype typical of mitotic arrest (Movie EV1).…”
Section: Resultsmentioning
confidence: 99%